2022
DOI: 10.1038/s41419-021-04481-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor SNAI2 exerts pro-tumorigenic effects on glioma stem cells via PHLPP2-mediated Akt pathway

Abstract: The current study aimed to investigate the effects associated with SNAI2 on the proliferation of glioma stem cells (GSCs) to elucidate its underlying molecular mechanism in the development of glioma. The expression of Snail family transcriptional repressor 2 (SNAI2) in glioma tissues was initially predicted via bioinformatics analysis and subsequently confirmed by reverse transcription quantitative polymerase chain reaction (RT-qPCR), which revealed that SNAI2 was highly expressed in glioma tissues as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Here, the high expressions of SNAI2 and TFDP1 were observed in the high-risk score patients; however, the expression of IKBKG and MCL1 was lower. Snail family transcriptional repressor 2(SNAI2), a member of the Snail family, was regarded as an epithelial-to-mesenchymal transition-inducing transcription factor (Peng et al, 2022); (Jin et al, 2022). Extensive research has shown that SNAI2 Frontiers in Pharmacology frontiersin.org plays a critical role in melanocytes, adipocytes, and germ cells, contributing to cell differentiation and tumor initiation (Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Here, the high expressions of SNAI2 and TFDP1 were observed in the high-risk score patients; however, the expression of IKBKG and MCL1 was lower. Snail family transcriptional repressor 2(SNAI2), a member of the Snail family, was regarded as an epithelial-to-mesenchymal transition-inducing transcription factor (Peng et al, 2022); (Jin et al, 2022). Extensive research has shown that SNAI2 Frontiers in Pharmacology frontiersin.org plays a critical role in melanocytes, adipocytes, and germ cells, contributing to cell differentiation and tumor initiation (Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…SNAI2 has been implicated in the diseases of melanocytes development and a variety of cancers ( Cobaleda et al, 2007 ). SNAI2 plays a crucial role in regulating T-cell lineages ( Pioli et al, 2016 ) and cancer cell stemness ( Chen et al, 2021 ; Peng et al, 2022 ), as well as modulating lapatinib resistance in HER2-positive breast cancer ( Hamalian et al, 2021 ) and enhancing 5-fluorouracil sensitivity in colorectal cancer ( Findlay et al, 2014 ). We developed a risk-scoring model for SKCM patients according to seven cuproptosis-related differential genes, using a training set to distinguish between low -risk and high -risk groups.…”
Section: Discussionmentioning
confidence: 99%
“…For sorting GCSs from U87 and LN229 cells by flow cytometry [ 29 ], after harvesting cells and resuspend with PBS, incubated the cells with anti-CD133 antibody (#60577S, Cell Signaling Technology) for 30 min at 4 ℃, protected from light. Following this, the cells were centrifuged at 1000 rpm for 5 min and subsequently resuspended in 100 μL of PBS.…”
Section: Methodsmentioning
confidence: 99%